Roussoella solani causing keratomycosis, with an observed both sexual and asexual morphs. Issue 9 (September 2017) - Mochizuki, Kiyofumi; Nishida, Takashi; Murata, Kazuhiro; Ishida, Kyoko; Sunada, Atsuko; Asari, Seishi; Ohkusu, Kiyofumi; Tanaka, Kazuaki
Abstract: We describe an 82-year-old male farmer who had diabetes mellitus with no history of ocular trauma by soil or plants and who developed a corneal infection due to a fungus. The organism was identified as Roussoella solani based on both the morphological characteristics and phylogenetic analysis using LSU and ITS nrDNA sequences. The sexual stage of R. solani is described and illustrated for the first time. The patient was treated successfully with a combination of topical and systemic voriconazole and micafungin. This case is the first report of keratomycosis caused by R. solani.